Quantifying India’s nitrogen, phosphorus, and potassium generation potential from agricultural and animal waste for sustainable nutrient management - Shanmugam, Vijayakumar; Kumar, Virender; Sundaram, Raman Meenakshi; Kumar, Rapolu Mahender; Peramaiyan, Panneerselvam; Murugaiyan, Varunseelan; Nayak, Amaresh Kumar (Frontiers in Agronomy, 2025)
India, the second-largest food producer and world’s largest livestock rearer, lacks comprehensive quantitative data on domestic organic waste generation, which hinders sustainable nutrient management and increases reliance on costly inorganic fertilizers. This study addresses this gap by quantifying the national and state-level potential of key organic wastes to bridge the country’s fertilizer demand. We quantify the annual generation of Nitrogen (N), Phosphorus (P), and Potassium (K) from various organic wastes and utilize these data to evaluate the potential for organic farming across Indian states by analyzing the nutrient balance between organic supply potential and inorganic fertilizer demand. Annually, India generates 667.7 million tons (MT) of animal waste, contributing 4.49 MT of N, 1.77 MT of P, and 3.31 MT of K. Cattle and buffalo account for over 90% of this generation. Additionally, 762.8 MT of crop residue is generated, primarily from rice, wheat, and sugarcane, yielding 4.55 MT of N, 0.53 MT of P, and 6.61 MT of K. Oil meal (23.3 MT) contributes an additional 1.51 MT of N, 0.25 MT of P, and 0.24 MT of K annually. Collectively, organic waste generates a massive resource of 10.6 MT of N, 2.6 MT of P, and 10.2 MT of K per year. Uttar Pradesh leads in organic nutrient generation, contributing 14.6% of N, 12.3% of P, and 18% of K, followed by Madhya Pradesh. On average, 10.1 tons of organic waste is available per-hectare in India, which could provide 75.6 kg of N, 18.0 kg of P, and 71.7 kg of K annually. However, significant region-specific nutrient imbalances persist. Among 36 states and union territories, 17 and 20 show negative N and P balances, respectively, while all states except Kerala have a positive K balance. The quantified state-level nutrient balance provides an essential roadmap for region-specific agricultural planning. Positive nutrient balance states should prioritize a rapid transition toward organic farming policies, while negative balanced states require strategic integrated nutrient management policies.